2017
DOI: 10.1039/c7se00381a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent consumption in non-catalytic alcohol solvolysis of biorefinery lignin

Abstract: a Lignin solvolysis in supercritical alcohols provides a method for producing a deoxygenated liquid bio-oil. Solvent consumption is however inevitable and due to the high cost of alcohols, relative to a bio-oil product, it can hinder commercial viability. In order to investigate the reactions of solvent consumption we studied solvolysis of biorefinery lignin in several primary alcohols. Lignin solvolysis in methanol, ethanol, 1-propanol and 1-butanol performed similarly with respect to bio-oil composition; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The same group later demonstrated that solvent decomposition occurs in three primary ways: (i) decomposition of the alcohol to gases through decarbonylation, (ii) the formation of light condensation products through condensation and dehydration reactions, and (iii) formation of ethers or esters through alcohol condensation with carboxyl and hydroxyl groups present in lignin. 26 Solvent consumption, together with char fouling, can be controlled to some extent by lowering the reaction temperature and reaction time. Choi et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group later demonstrated that solvent decomposition occurs in three primary ways: (i) decomposition of the alcohol to gases through decarbonylation, (ii) the formation of light condensation products through condensation and dehydration reactions, and (iii) formation of ethers or esters through alcohol condensation with carboxyl and hydroxyl groups present in lignin. 26 Solvent consumption, together with char fouling, can be controlled to some extent by lowering the reaction temperature and reaction time. Choi et al…”
Section: Introductionmentioning
confidence: 99%
“…al. 25,26 A second similarity relates to the primary objective, which is in all cases to (partially) deoxygenate and crack the lignin, thereby necessarily requiring severe (i.e., supercritical) process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…While interesting from a scientific stance, such diluted feeds would require an unrealistically high capital expenditure (CAPEX), given that CAPEX scales quite well with total volume/mass flow through the plant. Moreover, were such ratios to be applied commercially, even seemingly insignificant solvent losses of a mere few percents at lab scale, arising from, for example, flashing or chemical conversion towards less useful compounds [19], would surely be considered unacceptably high.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin-solvent reactions may also play a role on inhibiting competitive repolymerization pathways. 48 For most cases, increasing the reaction time from 20 to 60 minutes led to an increase of the lower M w fractions due to the subsequent oxidation of the lignin fragments solubilized in ethanol, which is known to happen at extended ozonation times. 54,55,59 The amounts of these fractions were greatly increased at the longer reaction times of 120 minutes (KL and ball-milled KL), likely accompanied by carbon loss due to CO 2 formation from over-oxidation.…”
Section: Product Yields and Macromolecular Propertiesmentioning
confidence: 98%
“…Overall, the use of catalysts adds extra complexity to lignin processing due to separation and reusability difficulties, fast deactivation, poisoning, high costs and irreversible morphologic changes in the case of heterogeneous catalysts. 44 Non-catalytic routes for the upgrading of technical lignins include pyrolysis [45][46][47] and solvolysis, [48][49][50][51][52] which despite the promising results, also need high temperatures to efficiently break down the structure and minimize repolymerization pathways. In addition, low monomer yields and high carbon losses to the gas, solid and aqueous phases are common.…”
Section: Introductionmentioning
confidence: 99%